2018
DOI: 10.1007/s11187-018-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of formalizing networks: new evidence from Italian SMEs

Abstract: Using a large sample of Italian small and medium-sized enterprises (SMEs), we investigate the effect of business cooperation realized through a "network contract" on the economic performance of network members. We find that establishing a formal business network has a positive effect on a firm's gross margin ratio and exports, but not on profits. The advantages of this type of networking are stronger in the cases of: smaller firms; firms operating in traditional markets; firms operating in turbulent markets; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Overall, theoretical research argued that being a member of a network is an important source of competitive advantage because it gives access to knowledge and resources at lower costs and helps to benefit from economies of scale (Gulati and Higgins 2003;Zaheer and Bell 2005;Watson 2012). Empirical research mainly confirmed the positive effect of network participation on firms' performance (Cisi et al 2020;Schoonjans et al 2013;Park et al 2010;Lechner et al 2006;Havnes and Senneseth 2001).…”
Section: Literature Review and Research Questionsmentioning
confidence: 80%
“…Overall, theoretical research argued that being a member of a network is an important source of competitive advantage because it gives access to knowledge and resources at lower costs and helps to benefit from economies of scale (Gulati and Higgins 2003;Zaheer and Bell 2005;Watson 2012). Empirical research mainly confirmed the positive effect of network participation on firms' performance (Cisi et al 2020;Schoonjans et al 2013;Park et al 2010;Lechner et al 2006;Havnes and Senneseth 2001).…”
Section: Literature Review and Research Questionsmentioning
confidence: 80%
“…In some cases, some dimensions of network complexity, as number of partners and geographic distance, were negatively associated with alliances performance (Rubino and Vitolla, 2018). In other cases, research has shown contrary results (Cisi et al, 2018). At the same time, it should be noted that the choice of different performance measures could conducted to different results as also highlighted in further research on the topic (Rubino et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The analyses are mainly theoretical or based on case studies (Mancini and Piscitelli 2018). However, Cisi et al (2018) found a positive effect between participation in a business network and the gross margin ratios and exports of firms in a study of a large sample of Italian SMEs that signed business network contracts drawn up in accordance with Italian regulations. Nevertheless, no effects on profits were observed.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 94%
“…We analysed profitability using the Return on sales indicator (ROS, Ebit margin over Revenues) and the Return on equity (net income/equity). These measures of performance are accepted in the literature and used in the empirical studies on networking (Cisi et al 2018;Hill et al 1992;Goerzen and Beamish 2005;Goerzen 2007). As capital structure and liquidity indicators, Liquidity ratio ([total current assetsinventories]/ short term debt) and Leverage ratio (financial debts/equity) were considered (Gulati 1995;Beamish and Lupton 2009;Franco 2011; Kawai 2012; Cantele and Vernizzi 2015).…”
Section: Variables Used In the Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation